Thromboelastometry assessment of mycophenolate mofetil effect on thrombotic risk in dogs with primary and secondary immune-mediated hemolytic anemia and by Erhlichia canis infection - Gorenstein, T.g. [UNESP]; Portilho, F.v.r. [UNESP]; Calobrizi, N.p. [UNESP]; Gonçalves, D.s. [UNESP]; Paes, A.c. [UNESP]; Takahira, R.k. [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2021)
This study aimed to identify, by means of thromboelastometry assessment, altered thrombotic risk in dogs with primary and secondary IMHA by E. canis infection after initiating the immunosuppressive therapy with mycophenolate mofetil. The animals’ screening was based on complete blood count (CBC), biochemical and urine tests. Dogs with moderate to severe anemia (hematocrit ≤ 25%) which showed symptoms of immune-mediated hemolysis, such as spherocytosis, positive saline agglutination, bilirubinuria and/or hemoglobinuria, were included. Blood and urine samples were collected at two different moments. The first sample (M1) was collected at the time of diagnosis, when hematocrit was lower or equal to 25% before treatment with mycophenolate mofetil (Accord ®); the second sample (M2) was collected after treatment with mycophenolate mofetil, when hematocrit was greater or equal to 30%. Five out of the twelve animals selected died before the end of the study. No reduction in thrombotic risk was observed in the animals treated with mycophenolate mofetil. The animals that presented hypocoagulation at the time of diagnosis showed the worst prognosis, and their reticulocyte count displayed a better prognostic value than their erythrocytes count at the time of diagnosis.

O objetivo deste estudo foi esclarecer se há alteração do risco trombótico em cães com anemia hemolítica imunomediada primária e secundária a E.canis, avaliado por meio da tromboelastometria, após início de tratamento com micofenolato de mofetila. A seleção dos animais foi baseada na avaliação de hemograma, exame bioquímico e urinálise. Cães com anemia moderada a severa (hematócrito ≤ 25%), com sinais de hemólise imunomediada, como esferocitose, aglutinação em salina positivo, bilirrubinúria e/ ou hemoglobinúria, foram incluídos. As amostras de sangue e urina foram coletadas em dois momentos diferentes. A primeira amostra (M1) foi coletada no momento do diagnóstico, quando o hematócrito era igual ou inferior a 25%, sem fazer uso do micofenolato de mofetila (Accord®), e o segundo momento (M2), após tratamento com micofenolato de mofetila, quando o hematócrito era igual ou maior que 30%. Doze animais foram selecionados, cinco morreram antes do término do estudo. Não houve diminuição do risco trombótico entre os animais tratados com micofenolato de mofetila; os animais que apresentaram menor coagulabilidade apresentaram pior prognóstico, e a contagem de reticulócitos apresentou melhor valor prognóstico do que a contagem de hemácias no momento do diagnóstico.
[Avaliação por tromboelastometria do efeito do micofenolato de mofetila no risco trombótico em cães com anemia hemolítica imunomediada primária e secundária à infecção por Erhlichia canis]
Keywords: hemoparasitosis; hemostasis; immunosuppression; prognosis; hemoparasitose; hemostasia; imunossupressor; prognóstico